Regarding safety of 33 KV underground source cable of Merul Badda 33/11 KV substation installed inside BRAC University new campus project - Brac University (Brac University, 2023)
This record consists of general correspondence regarding safety of 33 KV underground source cable of Merul Badda 33/11 KV substation installed inside BRAC University new campus project.